Variable speed drives controllers and troubleshooting - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The VARIABLE SPEED DRIVES: Controllers and Troubleshooting training program, or unit, is designed to familiarize trainees with general procedures for using a variable speed drive controller to troubleshoot system problems and for troubleshooting problems in the controller itself. After completing this program, the trainees should be able to describe how to safely use a variable speed drive controller to locate basic system problems. They should also be able to explain how to use a test point checklist to troubleshoot a variable speed drive controller and how to test the major components of the controller.
Keywords: Variable speed drives; Electric driving